Integrated CAD by Optimization: Architecture, Engineering, Construction, Urban Development and Management - Chakrabarty, B. K (Springer International Publishing AG, 2022)
This book presents range of topics concerning integrated CAD (including Optimization) for use in Architecture (including Planning), Civil Engineering and Construction (AEC), and thus, helps introduce a full-length treatment of the subject, enabling practitioners to adopt an Integrated Computer-Aided Design Approach in their professional activity. The book gives to readers an understanding of the main elements of CAD, highlighting the importance of integrating these elements and the applicability of Integrated CAD in AEC. Many examples and problems (including Optimization) are included to help professionals and students to develop and apply such tools in solving problems in AEC field. Adopts a problem solving approach in planning, design, and management stressing IT and Computer Application in AEC sector as a whole;Emphasizes resource-efficiency and social equity in problem solution in the AEC sector in general, and in urban development and management in particular;Stresses optimization and an integrated approach covering all components, including costs, affordability and environmental factors, scarcity of resources, and resolution of conflicting interests;Includes an accessible overview and source codes of C++ and Auto Lisp programs needed to carry out design analysis, optimization and drafting-drawing in an integrated manner.